The Pharmacogenetics of Cytochrome P450 2C19 Enzymes - Effects on Clopidogrel and Proton Pump Inhibitors - Yusmiati Yusmiati; Dewi Muliaty (The Indonesian Biomedical Journal, 2014)
BACKGROUND: Cytochrome P450 (CYP) enzymes play important roles in human, including drug metabolism. CYP2 is the largest family of human CYP, with its sequence comprising almost one third of all CYP sequences, and responsible for the metabolism of approximately 2% of clinically administrated drugs. One of the most important enzymes in this family is the CYP2C19 enzyme. The CYP2C19 gene is polymorphic, and the variation is common especially in the Asian population.CONTENT: CYP2C19 is responsible for the metabolism of various drugs, including proton pump inhibitors (PPIs) such as omeprazole and lansoprazole, psychotropic drugs including diazepam and imipramine, anticonvulsants such as phenobarbital and mephenytoin. and the recently most studied the anti-platelet drug, clopidogrel, and many others. Drugs metabolized predominantly by this enzyme like clopidogrel and PPIs might be much affected by the genotype status of CYP2C19. Clopidogrel is a pro-drug requiring a group of enzymes to convert to its active form, particularly the CYP2C19. PPIs are metabolized to its inactive metabolites mainly by CYP2C19 in the liver. Some PPIs are inhibitor of CYP2C19 enzymes, and interaction of PPIs and clopidogrel has been widely studied.SUMMARY: The association of CYP2C19 genotypes with the plasma level of active clopidogrel and platelet reactivity in individual taking this drug is well-established. Although conflicting results still exist for the association of CYP2C19 genotypes to the clinical outcomes of clopidogrel therapy, this effect seems to be consistent in patients receiving clopidogrel for coronary stents. Due to the interaction of certain PPIs and clopidogrel, the use of PPIs other than omeprazole is recommended, especially for patients taking dual anti platelet therapy of clopidogrel and aspirin.KEYWORDS: pharmacogenetics, CYP2C19, proton pump inhibitors, clopidogrel